Singing Krishna : Sound Becomes Sight in Paramanand's Poetry. - Sanford, A. Whitney (State University of New York Press, 2008)
"Singing Krishna introduces Paramanand, one of north India's greatest medieval poet-saints, whose poetry has been sung from the sixteenth century to the present in ritual service to the Hindu deity Krishna. A. Whitney Sanford examines how hearing Paramanand's poetry in ritual context serves as a threshold for devotees between this world and Krishna's divine world. To "see Krishna" is a primary goal of the devotee, and Paramanand deftly constructs a vision through words. Sanford employs the dual strategies of interpreting Paramanand's poems - which sing the cycles of Krishna's activities - and illustrating the importance of their ritual contexts. This approach offers insight into the nature of the devotional experience that is not accessible by simply studying the poetry or rituals in isolation. Sanford shows that the significance of Paramanand's poetry lies not only in its beauty and historical importance but finally in its capacity to permit the devotee to see through the ephemeral world into Krishna's world."--Jacket.